P-005 After MR Selection, Final Infarct Volume is Independent of Time to Thrombectomy for Anterior Large Vessel Occlusion Stroke. (29th July 2016) - Cristiano, B; Pond, M; Basu, S; Oyoyo, U; Jacobson, J
Abstract : Purpose: With thrombectomy for anterior circulation large vessel occlusion (ACLVO) stroke, time to recanalization is considered important, but collateral status may be a greater driver of outcome than time. We tested the hypothesis that patients with ACLVO stroke who present with a small core infarct on DWI would show similar good outcomes after thrombectomy, regardless of time from onset. Materials and methods: A cohort of 49 patients treated with thrombectomy after MR selection for ACLVO stroke from 11/1/2012 until 5/15/2015 was retrospectively reviewed. Patients were selected for thrombectomy based on DWI screening with presentation core volume ≤100 age considered favorable. Patients were divided into early (n = 24) or extended (n = 25) treatment groups, with intention to treat ≤6 hours = early, and comparisons made with final infarct volume the primary outcome. Results: Baseline characteristics were similar (early versus extended), including admission NIHSSS (IQR 13–19 versus 11–18). Recanalization ≥ TICI2B was 79% and 83% respectively. There was no significant difference in median final infarct volume (16 mL versus 22 mL, estimated difference +4 mL [95 CI: –13 – +19], p = 0.61) or median infarct growth (1 mL versus 5 mL, estimated difference 1.0 mL [95 CI: –7.0 – +10], p = 0.71). For decision to treat up to 20 hours after onset, time did not correlate with final infarct volume, Figure 1 . Similar rates of complications and mortality were observed. Conclusion: Using MR selection, similar good outcomes after thrombectomy for ACLVO stroke may be achieved well beyond 6 hours. Disclosures: B. Cristiano: None. M. Pond: None. S. Basu: None. U. Oyoyo: None. J. Jacobson: 4; C; GeneLux.